Necrotizing Lung Infection Caused by the Protozoan Balantidium coli - Sat Sharma; Godfrey Harding (Canadian Journal of Infectious Diseases)
Balantidium coli, a ciliated protozoan, is well known to cause intestinal infection in humans. Extraintestinal spread to the peritoneal cavity and genitourinary tract has rarely been reported. There have also been a few cases of lung involvement from this parasite. A case of B coli causing a thick-walled right upper lobe cavity in an organic farmer who had contact with aerosolized pig manure is reported. Bronchoalveolar lavage fluid examined for ova and parasite revealed trophozoites of B coli in large numbers. Treatment with doxycycline hyclate led to marked improvement. Necrotizing lung infection caused by the protozoan B coli should be considered in individuals who report contact with pigs.